A Monthly Quiz. Issue 11 (1st November 2017) - Unknown
Abstract : Certification Corner lets Opflow readers sharpen their skills with a quick quiz of terminology, regulations, practices, and formulas pertinent to water/wastewater distribution system and treatment plant operations.